Expressional Profiling of Carpet Glia in the Developing Drosophila Eye Reveals Its Molecular Signature of Morphology Regulators - Ho, Tsung-Ying; Wu, Wei-Hang; Hung, Sheng-Jou; Liu, Tsunglin; Lee, Yuan-Ming; Liu, Ya-Hsin (Frontiers in Neuroscience, 2019)
Homeostasis in the nervous system requires intricate regulation and is largely accomplished by the blood-brain barrier (BBB). The major gate keeper of the vertebrate BBB is vascular endothelial cells which form tight junctions (TJs). To gain insight into the development of the BBB, we studied the carpet glia, a subperineurial glial cell type with vertebrate TJ-equivalent septate junctions, in the developing Drosophila eye. The large and flat, sheet-like carpet glia, which extends along the developing eye following neuronal differentiation, serves an easily accessible experimental system for understanding the cell types exhibiting barrier function. We profiled transcribed genes in the carpet glia using targeted DNA adenine methyl-transferase identification followed by next-generation sequencing (targeted DamID-seq) and found that the majority of genes expressed in the carpet glia function in cellular activities related to its dynamic morphological changes in the developing eye. To unravel the morphology regulators, we silenced genes selected from the carpet glia transcriptome using RNA interference. The Rho1 gene encoding a GTPase was previously reported as a key regulator of the actin cytoskeleton. The expression of the pathetic (path) gene encoding a solute carrier transporter in the developing eye is specific to the carpet glia. Reduced expression of Rho1 severely disrupted the formation of intact carpet glia, and silencing path impaired the connection between the two carpet glial cells, indicating the pan-cellular and local effects of Rho1 and Path on carpet glial cell morphology, respectively. Our study molecularly characterizes a particular subperineurial cell type and provides a resource for further understanding of the cell types comprising the BBB.